2020
DOI: 10.3390/sports8090127
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Initial Muscle Strength Level on Sports Performance Changes in Collegiate Soccer Players

Abstract: The purposes of this study were to investigate effects of partial block periodized strength training on physical performance and to examine relationships between initial muscle strength measured with isometric mid-thigh pull (IMTP) and performance changes after 7 weeks of strength training. Seventeen collegiate male soccer players participated. Initial muscle strength was determined using IMTP while physical performance included 10 m and 20 m sprints and static vertical jump with a polyvinyl chloride pipe (SJ0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 25 publications
3
13
0
Order By: Relevance
“…Power is another important factor in physical performance for soccer [1,6,14]. High power production can provide performance advantages for sprinting and jumping in soccer players [8,9,28,29]. Our study provided additional evidence for substantial relationships among the 10 m sprint, SJ0, SJ20, and CMJ0, PP, and PPa.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Power is another important factor in physical performance for soccer [1,6,14]. High power production can provide performance advantages for sprinting and jumping in soccer players [8,9,28,29]. Our study provided additional evidence for substantial relationships among the 10 m sprint, SJ0, SJ20, and CMJ0, PP, and PPa.…”
Section: Discussionsupporting
confidence: 52%
“…It should also be noted that strength level plays a role in power production and soccer-related physical characteristics such as sprinting and jumping [6,7,29]. For example, Ishida et al [29] reported that strength was shown to be positively related to power production and sprint ability. However, care should be taken when improving power production associated with physical performance in soccer players.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the collegiate soccer schedule, block periodization may be appropriate when targeting specific training effects in preparation for in-season physical demands and time constraints. However, evidence also indicates that training status can influence gains in physical performance characteristics [ 12 , 13 , 14 , 15 ]. Evidence [ 12 , 14 ] indicates that athletes with higher initial maximum strength levels have been shown to gain maximum strength at a slower rate (10–15%) compared to weaker athletes.…”
Section: Introductionmentioning
confidence: 99%
“…However, evidence also indicates that training status can influence gains in physical performance characteristics [ 12 , 13 , 14 , 15 ]. Evidence [ 12 , 14 ] indicates that athletes with higher initial maximum strength levels have been shown to gain maximum strength at a slower rate (10–15%) compared to weaker athletes. Thus, it may be beneficial for sport scientists and strength and conditioning coaches to understand the effects of short-term block-style programming on performance changes based on training status.…”
Section: Introductionmentioning
confidence: 99%
“…The acceleration phase is a key component of sprinting. In several sport activities (e.g., track and field and team sports), sprinting is not only substantial to reach maximal speed but also, and more importantly, to cover a given distance in the lowest time [ 1 , 2 ]. To effectively display this skill, large forward acceleration is needed.…”
Section: Introductionmentioning
confidence: 99%